Notes to Philosophy 167: Class 2 -- 16th Century Astronomy: Copernicus and Tycho Brahe -- Part 6. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Copernicus and Ibn al-Shir (d. 1375); Generally corresponds to the video segment: Class 2, Part 6.